Screening of the LAMB2, WT1, NPHS1, and NPHS2 Genes in Pediatric Nephrotic Syndrome - Abid, Aiysha; Shahid, Saba; Shakoor, Madiha; Lanewala, Ali A.; Hashmi, Seema; Khaliq, Shagufta (Frontiers in Genetics, 2018)
Abstract: Mutations in the NPHS1, NPHS2, LAMB2 and the WT1 genes are responsible for causing nephrotic syndrome (NS) in two third of the early onset cases. This study was carried out to assess the frequencies of mutations in these genes in a cohort of pediatric NS patients. A total of 64 pediatric familial or sporadic SRNS cases were recruited. Among these, 74% had a disease onset of up to three years of age. We found one homozygous frameshift mutation in the NPHS1 gene in one CNS case and two homozygous mutations in the NPHS2 gene. Six mutations in four cases in the LAMB2 gene were also identified. No mutation was detected in the WT1 gene in isolated SRNS cases. LAMB2 gene missense mutations were segregating in NS cases with no extra-renal abnormalities. Analysis of the population genomic data (1000 genome and gnomAD databases) for the prevalence estimation revealed that NS is more prevalent than previously determined from clinical cohorts especially in Asian population compared with overall world populations (prevalence worldwide was 1in 189036 and in South-Asian was 1in 56689). Our results reiterated a low prevalence of mutations in the NPHS1, NPHS2, LAMB2 and WT1 genes in the studied population from Pakistan as compared to some European population that showed a high prevalence of mutations in these genes. This is a comprehensive screening of the genes causing early onset NS in sporadic and familial NS cases from South Asia suggesting a more systematic and robust approach for mutation identification in all the 45 disease-causing genes in NS in our population is required.